Analisis Efektivitas Organisasi dalam Upaya Penanggulangan Bencana Coronavirus Disease 2019 (Covid-19) di Kota Bandar Lampung (Studi Pada Gugus Tugas Percepatan Penanganan Covid-19 Kota Bandar Lampung) - Tiurma Mutiara; Nana Mulyana; Dewie Brima Atika (Jurnal Administrativa, 2023)
The large number of COVID-19 cases in Indonesia requires the Government through the District Government to form a Gugus Tugas Percepatan Penanganan COVID-19 Kota Bandar Lampung with the aim of suppressing or curbing the increase in cases of COVID-19 in the City of Bandar Lampung. The purpose of this study is to obtain a description of the effectiveness and identify supporting and hindering factors of the Gugus Tugas Percepatan Penanganan COVID-19 Kota Bandar Lampung in efforts to deal with the COVID-19 disaster. The overall research results of the Gugus Tugas Percepatan Penanganan COVID-19 Kota Bandar Lampung are quite effective in implementing efforts to combat the COVID-19 disaster. Then the supporting factor of the Gugus Tugas Percepatan Penanganan COVID-19 Kota Bandar Lampung is the readiness of good human resources and the large number of members, while the hindering factor is the lack of community participation and the state of damaged facilities and infrastructure.